(3cJGH aj Yde GdcdGes
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3ef Cgd ReGffG YGOdjf Yf SHjdg aGSJNQJ Gddg JYGdi Ydi ELGHJg HeG SCdfi eY eG cfJ bO PgH Edjg ef LeY cJGH s
(3BNQgG (B:s
(3ef HGH PcQ YjhH GdjghO hGdfUGQi hGdeLhS (B: (3hEfi deG TQWI GdGNJUGQ YOdJ Yf GdJWhjd hajg caGjI def MaXg hageg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds